2016
DOI: 10.3892/or.2016.4829
|View full text |Cite
|
Sign up to set email alerts
|

A new non-muscle-invasive bladder tumor-homing peptide identified by phage display in vivo

Abstract: Bladder cancer is common and widespread, and its incidence is increasing. Many new diagnostic methods combined with state-of-the-art technology have been introduced in cystoscopy to collect real-time images of the bladder mucosa for diagnosis, but often miss inconspicuous early-stage tumors. Fluorophore-labeled peptides with high sensitivity and specificity for cancer would be a desirable tool for the detection and treatment of tiny or residual bladder tumors. Phage display and the human non-muscle-invasive bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The tumor-specific peptide PLSWT7 was selected by phage display technology. Several peptides, such as CSNRDARRC [20], PLZ4 [21], and NYZL1 [16], show effective binding activity with BC-specific tumors; however, CSNRDARRC and PLZ4 were screened from muscle-invasive BC cell lines, whereas NMIBC accounts for 70% of all patients with BC. NYZL1 was screened from NMIBC cell lines, but in vivo studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor-specific peptide PLSWT7 was selected by phage display technology. Several peptides, such as CSNRDARRC [20], PLZ4 [21], and NYZL1 [16], show effective binding activity with BC-specific tumors; however, CSNRDARRC and PLZ4 were screened from muscle-invasive BC cell lines, whereas NMIBC accounts for 70% of all patients with BC. NYZL1 was screened from NMIBC cell lines, but in vivo studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…For the selection of BC-binding phage clones, the Ph.D.-C7C Phage-display Peptide Library Kit (New England Biolabs, Beverly, MA, USA) was used as previously described [16]. Subcutaneous tumor-bearing mice received 3 × 10 10 plaque forming units (PFUs) of the phage peptide library via tail vein injection.…”
Section: In Vivo Phage-display Selection Of Tumor-targeting Clonesmentioning
confidence: 99%
“…Yang et al successfully isolated and identified a peptide (CSSPIGRHC) with high affinity and specificity targeting to bladder cancer cell BIU-87 by phage display. The peptide synthesized and conjugated with FITC provides a promising diagnostic imaging approach for bladder cancer in humans (Yang et al 2016 ). Dysplasia is a pre-malignant status in Barrett’s esophagus that is difficult to detect on screening endoscopy because of its flat architecture and patchy distribution.…”
Section: Potential Applications Of Targeting Peptidesmentioning
confidence: 99%
“…The previous studies demonstrated that they have the ability to specifically bind to bladder tumor tissue. 38 , 39 , 40 CQDGRMGFC peptide was synthesized by a one-bead, one-compound combinatorial chemistry approach. After conjugating with Cy5.5, the molecular fluorescent tracer selectively accumulated in bladder tumor tissue of patient-derived xenograft mouse models.…”
Section: Main Textmentioning
confidence: 99%